2014
DOI: 10.1103/physrevb.89.140504
|View full text |Cite
|
Sign up to set email alerts
|

Spin-singlet superconductivity with a full gap in locally noncentrosymmetric SrPtAs

Abstract: We report 195 Pt-NMR and 75 As-NQR measurements for the locally non-centrosymmetric superconductor SrPtAs where the As-Pt layer breaks inversion symmetry while globally the compound is centrosymmetric. The nuclear spin lattice relaxation rate 1/T 1 shows a well-defined coherence peak below T c and decreases exponentially at low temperatures. The spin susceptibility measured by the Knight shift also decreases below T c down to T < T c /6. These data together with the penetration depth obtained from the NMR spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 26 publications
6
39
0
Order By: Relevance
“…A coherence peak below T c and an exponential decay as temperature decreases were observed. 10 These results were interpreted in connection with an s-wave pairing symmetry with a gap 2∆ 0 = 3.85k B T c , a value relatively high compared to the BCS standard. More recently, spinlattice relaxation rate 1/T 1 of 75 As was measured in two different polycrystalline samples of SrPtAs.…”
Section: 4mentioning
confidence: 85%
“…A coherence peak below T c and an exponential decay as temperature decreases were observed. 10 These results were interpreted in connection with an s-wave pairing symmetry with a gap 2∆ 0 = 3.85k B T c , a value relatively high compared to the BCS standard. More recently, spinlattice relaxation rate 1/T 1 of 75 As was measured in two different polycrystalline samples of SrPtAs.…”
Section: 4mentioning
confidence: 85%
“…Furthermore the f -wave pairing state is a triplet of the type √ 2(↑↓ + ↓↑). Therefore this state can not be excluded by a suppressed Knight-shift in the superconducting phase found by Matano et al 9 Indeed, in this compound, a Hebel-Slichter peak or a retardation of the decay in 1/T 1 T does not imply conventional s-wave superconductivity. Furthermore, to eliminate line nodes in the order parameter, a corresponding model is included.…”
Section: Nuclear Relaxation Ratementioning
confidence: 96%
“…Parallel to our work, Matano et al 9 performed NMR/NQR experiments on SrPtAs. While their 75 As T 1 relaxation data are consistent with ours with respect to the evidence for a fully gapped superconducting state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a detailed experimental investigation of QPI in SrPtAs should be able to discriminate between the theoretically proposed gap symmetries. This is particularly desirable because recent NMR and NQR experiments [4] suggest a fully gapped spin singlet state.…”
Section: After Inversionĝmentioning
confidence: 99%
“…The momentum dependence of these unconventional pair states was investigated theoretically by Goryo et al [3] and it was found that even A 1g , E g and odd A 2u states are viable candidates. However sofar there is only few experimental evidence to discriminate between them [4].…”
mentioning
confidence: 99%